2022
DOI: 10.1101/2022.09.06.506695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-risk microbial signatures are associated with severe parasitemia in controlledPlasmodiuminfections of both humans and rhesus macaques

Abstract: While functions of the gastrointestinal (GI) microbiome include maintenance of immune homeostasis and protection against infectious disease, its role in determining disease severity during Plasmodium infection has been limited to mouse models and observational human cohorts. Here, we performed controlled Plasmodium infection in both humans and rhesus macaques (RMs) to experimentally determine the impact of GI microbiome composition on disease progression. Through analysis of serially collected microbiome sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Bifidobacterium is associated with decreased Plasmodium parasitemia 6,18 . Bifidobacterium species are prevalent probiotic bacteria that confer myriad health benefits which have a role in antiinfection, anti-cancer, anti-inflammation, anti-obesity, and others 75 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bifidobacterium is associated with decreased Plasmodium parasitemia 6,18 . Bifidobacterium species are prevalent probiotic bacteria that confer myriad health benefits which have a role in antiinfection, anti-cancer, anti-inflammation, anti-obesity, and others 75 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that gentamicin, including other antibiotics, could significantly decrease the severity of malaria in mice 11 . Bifidobacterium is a common probiotic that confers health benefits 23 , B. adolescentis exerts anti-inflammatory properties in the gut via inhibition of NF-κB activation and lipopolysaccharide secretion 24 , and Bifidobacterium has been correlated with protection from P. falciparum infection and Py hyperparasitemia 6,18 . To determine the ability of these bacteria to mitigate severe malaria, hyperparasitemia-susceptible CR mice were gavaged daily from −7 to 7 days post-infection (p.i.)…”
Section: Hyperparasitemia-susceptible Mice Have Enriched Microbial Me...mentioning
confidence: 99%
See 1 more Smart Citation